IMPLEMENTATION IN THE HOSPITAL TREATMENT ROOM OF WEIGH-IN PATIENT RECEIVING WITH BEDSIDE HANDOVER METHOD - Rusmegawati; Lestari, Agustina; Negara, Candra Kusuma (Sean Institute, 2022)
The methodology for employing the bedside handover method while deploying patient receiving weighers between shifts is a set of instructions for doing so. This study aims to apply the bedside handover approach to patients receiving weights in hospital inpatient rooms. Action research, which is conducted in one cycle, is the research method used. The data gathering techniques included a focus group discussion guide, a patient satisfaction survey, a nurse work satisfaction survey, and an observation format. The 15 nurses who took part in this study were chosen using the purposive sample method. Both quantitative and qualitative statistical tests were used to assess the data on both a qualitative and quantitative level. This study developed a plan for implementing acceptable patient weights utilizing the bedside handover approach in hospital inpatient rooms. This study advised the hospital administration to test the draft protocol for the bedside handover approach to be used as a standard protocol.